2014
DOI: 10.1002/chem.201404275
|View full text |Cite
|
Sign up to set email alerts
|

Picolinamides as Effective Ligands for Copper‐Catalysed Aryl Ether Formation: Structure–Activity Relationships, Substrate Scope and Mechanistic Investigations

Abstract: The use of picolinic acid amide derivatives as an effective family of bidentate ligands for copper-catalysed aryl ether synthesis is reported. A fluorine-substituted ligand gave good results in the synthesis of a wide range of aryl ethers. Even bulky phenols, known to be very challenging substrates, were shown to react with aryl iodides with excellent yields using these ligands. At the end of the reaction, the first examples of end-of-life Cu species were isolated and identified as Cu(II) complexes with severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 84 publications
2
34
0
Order By: Relevance
“…In our previous investigation we observed that the catalytic activity increased using ligands bearing electron-withdrawing substituents on the phenyl ring. 43 Similar observations can be made for the results in Figure 1. Ligands L3 or L4, substituted with electronwithdrawing groups are generally more effective than L2 and L1.…”
Section: Arylation Of Phenolssupporting
confidence: 82%
See 3 more Smart Citations
“…In our previous investigation we observed that the catalytic activity increased using ligands bearing electron-withdrawing substituents on the phenyl ring. 43 Similar observations can be made for the results in Figure 1. Ligands L3 or L4, substituted with electronwithdrawing groups are generally more effective than L2 and L1.…”
Section: Arylation Of Phenolssupporting
confidence: 82%
“…This is true using either base, but the Scheme 2: Substrate scope: isolated yields in i-PrOAc (bold) and MeCN (italics, from ref. [ 43]); X = I, if not otherwise specified difference between the ligands is accentuated using K3PO4 (Figure 1b). In this case, ligand L1 is always considerably less effective than the others, whilst using Cs2CO3 its efficacy is sometimes only a little inferior ( Figure 1a).…”
Section: Arylation Of Phenolsmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19] We have also reported the uses of aluminium picolinamides for the ring-opening polymerisation of rac-lactide for use in the preparation of coloured polymeric materials 20 and picolinamide ligands as effective ligands for copper-catalysed aryl ether formation. 21 Herein, we report the reactions of picolinamide ligands with titanium(IV) precursors and discuss the structural properties of the potential intermediates. The reactions give titanium complexes with the ligand bound as either the amide or iminolate, in which the ligand is exclusively bound N,O.…”
Section: Introductionmentioning
confidence: 99%